Simulating the Dynamics of E-waste Production from Mobile Phone: Model Development and Case Study of Rwanda - Rutebuka, Evariste; Zhang, Lixiao; Pang, Mingyue (Journal of Environmental Accounting and Management, 2026)
Mobile phone sales and stocks showed an exponential growth in the past years globally and the annual number of mobile phones produced surpassed one billion in 2007. This soaring growth of related e-waste deserves sufficient attentions paid to it regionally and globally, since 40% of its total weight is made from metallic, of which 12 elements are identified to be highly hazardous. Different methods from different part of the world have been used to estimate the obsolete mobile phones but none has developed a dynamic model and handled the discrepancy resulting from improper approach and error in the input data. This study aimed to develop a comprehensive dynamic system model for simulating the dynamism of e-waste production from mobile phone specifically for African developing countries and to prevail over the previous errors. The logistic model method combined with Stella program were used to carry out this study. Then the simulation for Rwanda was conducted and compared with others countries’ results as model testing and validation. The results showed that Rwanda produced about 1.5 million obsolete mobile phones with 125 tons of waste in 2014 and e-waste production peak would appear in 2017. It is expected to reach 4.2 million obsoletes with 352 tons by 2020 along with environmental impact intensity of 21 times of 2005. Moreover, e-waste management policy for developing countries specifically for Rwanda has been suggested to reduce environmental impact up to 40% in 2020 and to 73% in 2030. The present study figured out the dynamism characteristic and outflow of the system design. It is concluded through the model testing and validation that the present dynamic model is competent and could deal with mobile phone e-waste production.